Conceptualizing nature-based science tourism: a case study of Seili Island, Finland - Räikkönen Juulia; Grénman Miia; Rouhiainen Henna; Honkanen Antti; Sääksjärvi Ilari E (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Nature-based tourism has been widely addressed, yet research on nature-based science tourism, founded on science, scientific knowledge, and/or engagement in scientific research, is still scarce. Drawing on tourist motivation, nature-based tourism, special interest tourism, and science tourism, a novel theoretical conceptualization of nature-based science tourism was developed. The framework identified three categories of science tourism with intensifying levels of tourists' interest in scientific knowledge and tourist engagement: tourism based on scientific knowledge, tourism with scientific adventure or volunteering, and scientific research tourism. In the empirical part, the framework was applied to Seili Island, Finland, and tourist motivation to nature-based science tourism was examined through a survey (n = 518). According to the results, tourists were interested in science and nature-based science tourism products, especially guided tours involving scientific interpretation, but also in intensive scientific excursions. Learning was a dominant motivation, but enjoying nature and escape and relaxation were also significant. When moving from guided tours to more intensive scientific excursions, motivations diversified; besides learning, other tourist motivations also need to be addressed in developing nature-based science tourism experiences. The study contributes to nature-based tourism and underresearched science tourism literature and provides practical implications for developing nature-based tourism.